Cannabidiol and naturalistic fallacy: it's natural so it's safe?. (2nd February 2023) - Lowe, Robyn
Abstract : The projected market value of the UK CBD industry looks to hit £1 billion by 2025. The statistics for its safety in animals are not easily obtainable. Many owners could be, and are suspected to be, using CBD products without a veterinary prescription. Many are using CBD as a 'natural' alternative, it is important to question and explore this relatively new trend to assess if natural really does mean safe and benign, and importantly if there is enough evidence base to warrant its use in veterinary medicine.